Internet- und mobilgestützte Interventionen bei psychischen Störungen: Implementierung in Deutschland aus ethischer Sicht - Rubeis, Giovanni; Steger, Florian (Der Nervenarzt, 2019)
Background: Internet and mobile-based interventions (IMIs) for mental disorders are seen by some authors as a step forward to narrow the treatment gap in mental health; however, especially in Germany professionals voice ethical concerns against the implementation of IMIs. The fact that there is broad evidence in favor of IMIs and that IMIs have already been implemented in several countries requires an ethical analysis to answer these concerns.ObjectiveThe objective is to tackle ethical issues connected to a possible implementation of IMIs for mental disorders in Germany and to point out possible solutions.Material and methodsWe conducted an ethical analysis using the criteria of well-being of patients, non-maleficence, justice, and patient autonomy, based on the empirical evidence.Results and conclusionThe ethical analysis showed that IMIs for mental disorders principally have a positive effect on the well-being of patients and have a low risk of impairment. Additionally, IMIs can minimize risk, improve justice, and strengthen autonomy of mentally ill patients. Despite the broad evidence, there are still research desiderates with respect to ethical aspects, e. g. patient information for mentally ill patients.